University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.6 - The Chain Rule - Exercises - Page 158: 10


$\frac{dy}{dx} = -27(4-3x)^{8}$

Work Step by Step

$y = u^{9}$ where, $u = (4-3x)$ Now, $\frac{dy}{du} = 9u^{8}$ $\frac{du}{dx} = -3$ So, $\frac{dy}{dx} = \frac{dy}{du} \times \frac{du}{dx}$ $\frac{dy}{dx} = -27u^{8}$ $\frac{dy}{dx} = -27(4-3x)^{8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.